2020
DOI: 10.1186/s13717-020-00247-4
|View full text |Cite
|
Sign up to set email alerts
|

Changing climate patterns risk the spread of Varroa destructor infestation of African honey bees in Tanzania

Abstract: Background Climate change creates opportune conditions that favour the spread of pests and diseases outside their known active range. Modelling climate change scenarios is oftentimes useful tool to assess the climate analogues to unveil the potential risk of spreading suitability conditions for pests and diseases and hence allows development of appropriate responses to address the impending challenge. In the current study, we modelled the impact of climate change on the distribution of Varroa d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…The species has also become more frequently found in city centers (Burger 2007). Our study, predicting range expansion of European beewolf, is in line with studies predicting range expansion of other honeybee pests (Cornelissen et al 2019;Giliba et al 2020). Together with models predicting the decline of suitable niche for bee species (Potts et al 2010;Goulson et al 2015;Imbach et al 2017), climate change can therefore adversely affect both future global bee diversity and the beekeeping industry.…”
Section: Discussionsupporting
confidence: 89%
“…The species has also become more frequently found in city centers (Burger 2007). Our study, predicting range expansion of European beewolf, is in line with studies predicting range expansion of other honeybee pests (Cornelissen et al 2019;Giliba et al 2020). Together with models predicting the decline of suitable niche for bee species (Potts et al 2010;Goulson et al 2015;Imbach et al 2017), climate change can therefore adversely affect both future global bee diversity and the beekeeping industry.…”
Section: Discussionsupporting
confidence: 89%
“…Such spatial variability in climatic factors, between regions and even between seasons, can create opportunities for the spread of different pests and pathogens beyond their ecological niches if not regularly monitored. Earlier studies have shown that changes in climate patterns and geographical variation have significantly impacted the distribution of V. destructor for the past 10 years in honey bee colonies of East Africa (Chemurot et al, 2016; Giliba et al, 2020; Muli et al, 2014). Particularly, Giliba et al (2020) demonstrated that changing climate patterns posed a high risk to the spread of the V. destructor mite in Tanzania.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that changes in climate patterns and geographical variation have significantly impacted the distribution of V. destructor for the past 10 years in honey bee colonies of East Africa (Chemurot et al, 2016; Giliba et al, 2020; Muli et al, 2014). Particularly, Giliba et al (2020) demonstrated that changing climate patterns posed a high risk to the spread of the V. destructor mite in Tanzania. Likewise, the varied prevalence and infestation levels of varroa in Ethiopia appears to be associated with such climatic and ecological variations among geographic regions, while further research is required to identify suitable and non‐suitable climatic factors to predict the potential risk of the parasite in the country.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the Varroa spp. (Mesostigmata mite) is a known parasite of honeybees [ 3 , 4 , 5 , 6 , 7 ]. Ectoparasites can harm hosts by feeding on their tissues and causing dermatitis, and some of them are vectors of pathogenic and life-threatening diseases.…”
Section: Introductionmentioning
confidence: 99%